Access to water for human consumption in the province of SaltaArgentina. Design of an indicator in the SIG context (2019)
This paper presents a spatial analysis of the accessibility to pure water for consumption purposes. The area estudied is Salta province, located in the Northwest Argentina. Based on data from the National Population and Housing Census (2010), an indicator is defined. This indicator incorporates three evaluation criteria: origin of water, potential of access and possession of water. Results show that a high percentage of the population of Salta has difficulties in accessing water, particularly in rural areas. The developed tool aims to contribute to the acknowledgement of the water problem and to promote a territorial approach in national, provincial and local management.